Design and Optimization of a Gripper Clamp - Mariana Cunha; Sofia Alves; Jose Costa (U.Porto Journal of Engineering)
Additive Manufacturing, among the many developing advanced manufacturing technologies, stands out as the one with the greatest potential for changing the distribution of manufacturing, society, and sustainability. To produce sustainable and competitive products, component material and design selection is an essential and critical topic in the industry. The production of parts designed using the Design for Additive Manufacturing methodology (DfAM) has grown in popularity in recent years. Topological optimization can be used as a design tool in the early stages of the design process to meet strength and endurance requirements on a component level. This study explores the topology optimization of a gripper clamp through nTopology and Fusion 360, using AISI 316L stainless steel as material, for possible production through Additive Manufacturing. The final component demonstrated reliable results.